Preferred anastomosis following choledochal cyst excision: A cross-sectional survey among pediatric surgeons - Jayakumar P; Selvakumar M; Meenakshi Sundari S; Rock Britto D (Asian Journal of Medical Sciences, 2023)
Background: Choledochal cyst (CC) is a cystic dilatation of various parts of the biliary tract that requires surgical intervention. Excision of the CC with biliary enteric anastomosis is the standard line of treatment. There are two types of biliary enteric anastomosis, hepaticojejunostomy (HJ), and hepaticoduodenostomy (HD). However, there is no consensus among surgeons regarding the preferred anastomosis technique. Aims and Objectives: In this study, we conducted a survey among pediatric surgeons in India to determine their preferred anastomosis technique following CC excision. Materials and Methods: A cross-sectional survey was conducted among pediatric surgeons in India by circulating a Google™ form containing information about their demographics and their preferred choice of anastomosis in the Indian Association for Pediatric Surgeons Official Telegram™ group called “Pediatric Surgery Academics.” The survey was done in June and July 2019. Results: A total of 53 (9.96%) pediatric surgeons responded to the survey. Among them, 47 (88.7%) were male and 6 (11.3%) were female pediatric surgeons. The mean age of the surgeons was 46.21, and the mean number of cases operated by pediatric surgeons was 28.49. Experience-wise, 8 (15.1%) had <5 years of experience, 14 (26.4%) had 5–10 years, 17 (32.1%) had 11–20 years, and 14 (26.4%) had more than 20 years of experience in pediatric surgery. In their practice, 32 (60.4%) had done both HJ and HD, 18 (34%) had done only HJ, and HD was done by 3 (5.7%) pediatric surgeons only. Pediatric surgeon’s preference of anastomosis was as follows, 27 (50.9%) inclined to HJ, 18 (34%) inclined to HD, and the remaining 8 (15.1%) inclined to both HJ and HD. Conclusion: This survey revealed that among pediatric surgeons in India, HJ is the preferred anastomosis technique following CC excision. However, further studies are required to determine the long-term outcomes of these techniques.